Eigenvalues and eigenfields of a corrugated gyrotron cavity with conducting walls - Tkachova, T.I.; Shcherbinin, V.I.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2018)
Electromagnetic analysis of a cylindrical gyrotron cavity with longitudinal wall corrugations is performed on the
basis of the approximate surface impedance model (SIM) and the full-wave spatial harmonic method (SHM). The
good convergence of SHM with respect to the number of spatial harmonics is shown. The perturbation approach is
extended to a cylindrical corrugated cavity with finite wall conductivity. With this approach attenuation of TE cavity
modes due to ohmic wall losses is investigated. For the TE8,3 mode, as an example, the number of corrugations,
which ensures reasonable accuracy of SIM, has been determined. For such number of corrugations, good agreement
between SIM and SHM is demonstrated for mode eigenvalue, eigenfields and attenuation. На основі наближеної поверхневої імпедансної моделі (SIM) та строгого методу просторових гармонік
(SHM) проведено електромагнітний аналіз циліндричного резонатора гіротрону з поздовжніми гофрами.
Показано добру збіжність методу SHM зі збільшенням числа просторових гармонік. Теорію збурень
узагальнено на випадок гофрованого резонатора гіротрону з кінцевою провідністю стінок. З її допомогою
досліджено згасання ТЕ-мод резонатора в результаті омічних втрат у стінках. Як приклад, для моди ТЕ8,3
визначено кількість гофрів, що забезпечує достатню точність SIM. Для такої кількості гофрів
продемонстровано добру згоду розрахунків SIM та SHM для власного значення моди, її власних полів та
загасання. На основе приближенной поверхностной импедансной модели (SIM) и строгого метода
пространственных гармоник (SHM) проведен электромагнитный анализ цилиндрического резонатора
гиротрона с продольными гофрами. Показана хорошая сходимость метода SHM с увеличением числа
пространственных гармоник. Теория возмущений обобщена на случай гофрированного резонатора
гиротрона с конечной проводимостью стенок. С ее помощью исследовано затухание ТЕ-мод резонатора в
результате омических потерь в стенках. В качестве примера, для моды ТЕ8,3 определено количество гофров,
обеспечивающее достаточную точность SIM. Для такого количества гофров продемонстрировано хорошее
согласие расчетов SIM и SHM для собственного значения моды, ее собственных полей и затухания.